ANALISIS PROSES PRODUKSI BETON CCSP PT.X MENGGUNAKAN LEAN MANUFACTURING DENGAN PENDEKATAN SIMULASI SISTEM - Muhammad Tsany Prasetyo (2020)
The increasing development that occurred in Indonesia, increasingly shows that Indonesia economic growth and competitiveness against rapid global changes. One of them is the construction of toll road access. Whereas toll roads can accelerate economic growth and economic equality. Based on the statistics from the Ministry of Public Works & Public Housing, over the past 5 years, the toll road development graph has always been increasing. This makes the needs an increase for toll road construction materials. Various efforts are needed for the relevant industry so that they can survive the competition in the industrial world. PT.X is a company that engages in the concrete industry. PT. X produces CCSP concrete which is a barrier on the toll road. In the making of CCSP concrete, is still wasteful. To overcome these problem, this research uses the Lean Manufacturing method. This research begins with Value Stream Analysis Tools, Value Stream Mapping, Fishbone Chart, then implement them using simulations. This research is expected to provide a better production system design. The result showed with improvement recommendations, the concrete production process time could decrease 41.94% from 88622 seconds to 51446 seconds. In addition, the output of the proposed simulation also increased by 74.65% from 29 units to 51 units.